Manuka honey activates the aryl hydrocarbon receptor: Implications for skin inflammation - Abdullah A. Alangari; Matin D. Ashoori; Wisam Alwan; Hannah R. Dawe; Brigitta Stockinger; Jonathan N. Barker; Emma Wincent; Paola Di Meglio (Elsevier, 2023)
Manuka honey (MH) is a complex nutritional material with antimicrobial, antioxidant and anti-inflammatory activity. We have previously shown that MH down regulates IL-4-induced CCL26 expression in immortalized keratinocytes. As MH contains potential ligands of the Aryl Hydrocarbon Receptor (AHR), a key regulator of skin homeostasis, we hypothesize that this effect is mediated via AHR activation. Here, we treated HaCaT cell lines, either stable transfected with an empty vector (EV-HaCaT) or in which AHR had been stable silenced (AHR-silenced HaCaT); or primary normal human epithelial keratinocytes (NHEK) with 2% MH for 24 h. This induced a 15.4-fold upregulation of CYP1A1 in EV-HaCaTs, which was significantly reduced in AHR-silenced cells. Pre-treatment with the AHR antagonist CH223191 completely abrogated this effect. Similar findings were observed in NHEK. In vivo treatment of the Cyp1a1Cre x R26ReYFP reporter mice strain's skin with pure MH significantly induced CYP1A1 expression compared with Vaseline. Treatment of HaCaT with 2% MH significantly decreased baseline CYP1 enzymatic activity at 3 and 6 h but increased it after 12 h, suggesting that MH may activate the AHR both through direct and indirect means. Importantly, MH downregulation of IL-4-induced CCL26 mRNA and protein was abrogated in AHR-silenced HaCaTs and by pre-treatment with CH223191. Finally, MH significantly upregulated FLG expression in NHEK in an AHR-dependent manner. In conclusion, MH activates AHR, both in vitro and in vivo, thereby providing a mechanism of its IL4-induced CCL26 downregulation and upregulation of FLG expression. These results have potential clinical implications for atopic diseases and beyond.